Dietary Recommendation in Diabetes Care: Carbohydrate Counting and Caloric Content of Nigerian Foods - Taoreed Azeez; Patience Chimah; Abdul F. Hassan; Yusuf Moradeyo; Ubong Umoren; Emmanuel Eguzozie (Advances in Food Technology and Nutrition Sciences, 2020)
The prevalence of diabetes mellitus is rising globally and even more in low and middle-income countries such as Nigeria. Optimal management of the disease is important to improve survival and prevent or delay its complications. Lifestyle management is a standard universal approach in optimizing the care given to diabetic patients. Dietary management is the central link in lifestyle modifications of individuals living with diabetes. Medical nutrition therapy (MNT) is a systematic therapeutic approach of as-sessing the nutritional needs of an individual, determining nutritional goals, counselling the clients on how to achieve the goals, prescribing and monitoring meal plans to achieve the goals. It is evidence-based, effective and highly recommended. All carers of the diabetes patient, including the health workers and the family members of the patients, need to have basic understanding of medical nutrition therapy but the efforts should be coordinated by licensed dietitians. There are evidences that adherence to prescribed calories is effective in the control of cardiovascular risk factors such as blood glucose, weight, lipid profile and blood pressure. However, prescription of calories should be based on thoughtful consideration of the nutritional needs, weight goal, personal preferences and tastes and cultural practices of individuals living with diabetes mellitus. Food pyramids give a graphical illustration on the recommended classes and servings of food. Six to eleven servings per day of carbohydrates, 3-5 servings per day of vegetables, 2-4 servings per day of fruit, 2-3 servings per day of dairy products and 2-3 servings per day of fish are the recommended proportions of the different classes of foods for an adult on an average of 2000 calories. Carbohydrate counting, taken with appropriate insulin dosing and physical activity, has been demonstrated to be effective in optimizing the glycaemic control of patients on multiple daily insulin injections. There are challenges in doing this in Nigeria due to lack of food labels. The caloric contents of common Nigerian foods are highlighted so as to help in achieving dietary goals.